Hubungan dukungan teman sebaya dengan konsumsi tablet tambah darah pada remaja putri - Muntabiah, Laela Hidayah Eka Maulida; Suratini, Suratini; Rahmat, Ibrahim (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Adolescent girls are a group vulnerable to anemia due to iron deficiency, especially during menstruation. Regular consumption of iron supplements is an important way to prevent anemia and support adolescent health. However, adherence to iron supplements remains low due to various factors, one of which is peer support Purpose: The aim of this study was to determine the relationship between peer support and the consumption of iron tablets. Metod: This quantitative research used a cross-sectional method. The data collection technique used total sampling. The sample size for this study was 50 respondents. Data analysis used the Chi-Square test. Results: The results of this study indicate that there is a relationship between peer support and the consumption of iron tablets in female adolescents (p value: 0.009 < 0.05) which means that the data that has been tested is said to be significant and the correlation coefficient is 0.037 which means that the correlation between good relationships Conclusion: There is a significant relationship between peer support and the consumption of iron tablets in adolescents. Keywords: Adolescents; Consumption Of Iron Tablets; Peer Support. Pendahuluan: Remaja putri merupakan kelompok yang rentan mengalami anemia akibat kekurangan zat besi, terutama selama masa menstruasi. Konsumsi tablet tambah darah secara rutin menjadi salah satu Upaya penting untuk mencegah anemia dan mendukung Kesehatan remaja. Namun, kepatuhan mengonsumsi TTD masih rendah karena berbagai factor, salah satunya adalah dukungan dari teman sebaya Tujuan: untuk mengetahui hubungan dukungan teman sebaya dengan konsumsi tablet tambah darah pada remaja putri. Metode: Penelitian kuantitatif dengan metode cross sectional. Teknik pengambilan data ini menggunakan total sampling. Sampel pada penelitian ini sebanyak 50 responden. Analisis data penelitian menggunakan uji Chi-Square. Hasil: Ada hubungan anatar dukungan teman sebaya dengan konsumsi tablet tambah darah pada remaja putri p value: 0.009<0.05 yang berarti data yang telah dilakukan uji dikatakan signifikan dan hasil korelasi koefien sebesar 0.037 yang berarti korelasi antara hubungan baik. Simpulan: Terdapat hubungan yang signifikan antara dukungan teman sebaya dengan konsumsi tablet tambah darah pada remaja. Kata Kunci: Dukungan Teman Sebaya; Konsumsi Tablet Tambah Darah; Remaja.